Digital valuation of radiologic attenuation indexes of normal anatomical structures and dental materials observed in panoramic images - López Videla-Montaño, Gianna; Rudolph-Rojas, Mauricio; Guzmán-Zuluaga, Carmen Lucía (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: the fast technological development applied to medical digital images has opened a new dimension in the qualitative and quantitative assesment of dental and skeletal components, as well as treatment control when biomaterials are used. The knowledge of the Mathematical Standard Profiles and biomaterials used allows the detection of structural alterations such as pathology and dental materials failures. Methods: direct digital panoramic images were taken and the numerical absoprtion value of anatomical structures and dental materials most commonly seen in panoramic images were analyzed. Results and conclusions: the gray tone scale varied from 0 to 255, corresponding to the value of the tones of pixels observable and dependent on electric current in Digital radiographic technology applied to maxillofacial area.